Application of Double Matrix Membrane Technology for Ion-Selective Electrodes - Wendzinski, Frank; Borchardt, Michael; Romberg, Bettina; Knoll, Meinhard (Analytical letters, 2003)
Double matrix membrane technology (DMM) is an excellent technique for creating inexpensive and robust electrochemical electrodes. In this report the use of DMM-electrodes to measure different ions (namely Ca 2+ , Mg 2+ , Cl − ) is described. The ion-selective membranes are basing on PVC and stabilized by deposition on a porous matrix. The authors determined the following characteristics of the ion-selective electrodes (ISEs): sensitivity; detection limit; linear range and selectivity coefficients. When changing the analyte concentration response time was lower than 30 s (Ca 2+ , Cl − ) or 1 min (Mg 2+ ). In the case of the determination of the selectivity coefficients it was considered in which concentrations the interfering ions naturally occur in physiological matrices, e.g., blood. In case of the chloride-selective electrode the discrimination of ascorbic acid and salicylate was investigated. The coefficients were evaluated by using the fixed interference method (FIM). The reproducibility of electrochemical characteristic was determined by investigating 120 mass-produced ammonium-selective electrodes. Furthermore, it was discovered that DMM-based potassium-selective electrodes may be stored stable for at least 4.5 years.